Determination of comorbidity index for high-risk patients with coronary artery disease before cardiac surgery - О. К. Gogayeva (Zaporožskij Medicinskij Žurnal)
The aim: to determine the comorbidity index before cardiac surgery in high-risk patients with coronary artery disease (CAD).